Terahertz high-TC superconductor photonics - Pang, Ietro Teng Chen (Nanyang Technological University, 2022)
There is a considerable research interest in Terahertz technologies due to their non-ionising and non-destructive radiation. This could be useful for many applications, such as non-invasive medical sensors and terahertz spectroscopy. To realise this potential, terahertz sensor is needed. Metamaterials such as asymmetric split rings can offer such capability thanks to the ultrasensitive Fano resonance due to the sensor's change in capacitance and inductor. Superconductors are unique material as it has zero DC resistance. By fabricating terahertz asymmetric split ring using superconductors, this setup can potentially realise the opportunity to control and tune the resonance of the metamaterial sensor. In this thesis, we investigate the use of ion-irradiation to induce damage to a d-wave YBCO superconductor to create a Terahertz Asymmetric Split Ring metamaterial on a Lanthanum aluminate substrate. We will also use this opportunity to gather the material characteristic of undamaged YBCO. Ion irradiated YBCO via Terahertz time-domain spectroscopy to study its conductivity and consider the use of numerical simulation to gain further insight into the film.